2012
DOI: 10.1534/genetics.111.133827
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for X-Linked Mutations Affecting Drosophila Photoreceptor Differentiation Identifies Casein Kinase 1α as an Essential Negative Regulator of Wingless Signaling

Abstract: The Wnt and Hedgehog signaling pathways are essential for normal development and are misregulated in cancer. The casein kinase family of serine/threonine kinases regulates both pathways at multiple levels. However, it has been difficult to determine whether individual members of this family have distinct functions in vivo, due to their overlapping substrate specificities. In Drosophila melanogaster, photoreceptor differentiation is induced by Hedgehog and inhibited by Wingless, providing a sensitive system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 109 publications
(135 reference statements)
0
25
0
Order By: Relevance
“…In a mosaic screen of the X chromosome (Legent et al, 2012), we recovered a mutation that prevents photoreceptor differentiation. In eye imaginal discs, clones of 3B1 mutant cells showed a cellautonomous lack of expression of the pan-neuronal marker Elav (Fig.…”
Section: Vps4 Is Required For R8 Survival and R1-r7 Differentiationmentioning
confidence: 99%
See 4 more Smart Citations
“…In a mosaic screen of the X chromosome (Legent et al, 2012), we recovered a mutation that prevents photoreceptor differentiation. In eye imaginal discs, clones of 3B1 mutant cells showed a cellautonomous lack of expression of the pan-neuronal marker Elav (Fig.…”
Section: Vps4 Is Required For R8 Survival and R1-r7 Differentiationmentioning
confidence: 99%
“…Although some studies have demonstrated that it contributes to signal termination through lysosomal EGFR degradation (Bache et al, 2006;Razi and Futter, 2006), other results argue that it enables receptor signaling from intracellular organelles (Miaczynska et al, 2004;Shilo and Schejter, 2011). Vps4 clones in Dronc mutant eye discs resemble clones lacking positive intracellular effectors of EGFR transduction, in which R8 cells fail to recruit additional photoreceptors (Legent et al, 2012). We found that the expression of lacZ reporters for two direct transcriptional targets of the EGFR pathway in R1-R7, argos (aos) (Golembo et al, 1996) and hedgehog (hh) (Rogers et al, 2005), was downregulated in Vps4 mutant clones (Fig.…”
Section: Vps4 Is Required For Egfr Signalingmentioning
confidence: 99%
See 3 more Smart Citations